2018
DOI: 10.1111/and.13064
|View full text |Cite
|
Sign up to set email alerts
|

Profertility effects of Shilajit on cadmium-induced infertility in male mice

Abstract: Shilajit is claimed as a Vajikarak (aphrodisiac) and used for the treatment of male infertility by traditional healers of the Indian subcontinent. Therefore, the present investigation was designed to assess the effectiveness of Shilajit for treatment of male infertility resulting from exposure to perilous chemicals. Effect of daily oral administration (p.o.) of Shilajit (50 mg, 100 mg and 200 mg/Kg BW) was investigated for a single spermatogenic cycle (35 days) in cadmium-induced (2 mg/Kg BW, p.o. for 35 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…This study concluded that Lunasia amara was a potential herb to enhance male fertility. Mishra et al demonstrated the profertility effects of Shilajit which is a compact humic substance commonly prescribed for genitourinary disorders, digestive disorders, and diabetes [ 78 ]. Toxicity induced by cadmium in Swiss albino mice was reverted after treatment with the water extract (50, 100, 200 mg/kg for 35 days).…”
Section: Plant Extract and Infertilitymentioning
confidence: 99%
“…This study concluded that Lunasia amara was a potential herb to enhance male fertility. Mishra et al demonstrated the profertility effects of Shilajit which is a compact humic substance commonly prescribed for genitourinary disorders, digestive disorders, and diabetes [ 78 ]. Toxicity induced by cadmium in Swiss albino mice was reverted after treatment with the water extract (50, 100, 200 mg/kg for 35 days).…”
Section: Plant Extract and Infertilitymentioning
confidence: 99%
“…Disturbed gonadal and hormonal functions are also postulated to play a crucial role in the testicular toxicity induced by cadmium. Previous studies have described that several substrates that can regulate steroidogenesis and exert therapeutic effects on cadmium-induced testicular toxicity, such as Feijoa, Shilajit and Moringa leaf ethanolic extracts [ 6 , 28 , 29 ]. The present study was conducted to evaluate the effect of cadmium on steroidogenesis, the quality and quantity of sperm, and the inflammatory response in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Disturbed hormonal production is presumed to play a major role in the pathogenesis of infertility and testicular dysfunction induced by cadmium [ 5 ]. According to some studies, Cd significantly decreases the serum testosterone (T) level by inhibiting the activities of steroidogenic enzymes [ 3 , 6 ]. Several mechanisms of cadmium-induced disruptions in hormone production have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The testis tissue is easily affected by oxidative stress because of its both high metabolic activity and membrane structure rich in polyunsaturated lipids (Vernet, Aitken, & Drevet, 2004). Earlier studies reported, following exposure to Cd, both an increase in abnormal sperm percentage and a decrease in the sperm motility and viability through increases in lipid peroxidation in the sperm membrane and consequently caused a dramatic change in the sperm fertilising potential in rats (El‐Demerdash et al, 2004; Mishra, Jain, & Singh, 2018). Similarly, Akinloye et al (2006) reported that Cd impaired the spermatogenesis by inducing systemic and cellular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Cd‐induced reproductive toxicity studies also frequently evaluate changes in testicular tissue appearance to confirm spermiotoxic effects. Deteriorations and vacuolisations in Sertoli cells and oedema in the interstitium have been heavily documented as the first indicators of spermatogenesis damage in Cd‐induced reproductive toxicity (De Souza Predes, Diamante, & Dolder, 2010; Mishra et al, 2018; Ren et al, 2012). Our histopathological results indicated that CdCl 2 treatment caused major structural variations such as degeneration, cellular losses, deformations and oedema in tissue and cell of testicle accompanied by poor sperm quality compared to the untreated control group.…”
Section: Discussionmentioning
confidence: 99%